Towards a Diachrony of Orality: The Beginning of the Dialogical Turn and Communicative Immediacy in 16th and 19th Century Translations of Plautus and Terence - Quesada, Santiago Del Rey (2020)
In this work the possibility of deriving diachronic conclusions from the study of conceptual orality in literature is tested. With this purpose, some theatrical translated texts from Plautus and Terence of the 16th and 19th centuries are compared. The research concentrates on syntactic strategies related to the beginning of the dialogical turn. Throughout the analysis I discuss whether mechanisms which shape oral textuality in theatrical literature in the 16th and in the 19th century are the same or they undergo significant variations across time. Furthermore, the influence of Latin source text in the constitution of fictional orality strategies within the corpus is considered.